The tadpole of Physalaemus orophilus from the Atlantic rainforest of southeastern Brazil (Amphibia, Anura, Leptodactylidae) - Pezzuti, Tiago Leite; Leite, Felipe Sá Forte; Silva, Douglas Henrique; Lourenço, Ana Carolina Calijorne; Baeta, Délio (Zootaxa, 2019)
The neotropical genus Physalaemus Fitzinger is currently composed by 48 species (Cardozo & Pereyra 2018). Recently, a phylogenetic analysis aiming to investigate the internal relationships of the genus recovered two major clades, the Physalaemus cuvieri and P. signifer clades (Lourenço et al. 2015). The following species groups were retrieved in the first clade: P. biligonigerus, P. cuvieri, P. gracilis, P. henselii, and P. olfersii groups (Lourenço et al. 2015). This proposal redefined the P. olfersii group including P. olfersii (Lichtenstein & Martens), P. soaresi Izecksohn, P. maximus Feio, Pombal, & Caramaschi, P. feioi Cassini, Cruz, & Caramaschi and P. lateristriga (Steindachner). The authors also allocated tentatively P. orophilus Cassini, Cruz, & Caramaschi, and P. insperatus Cruz, Cassini, & Caramaschi in the P. olfersii group due to their morphological similarity with the other species (Cruz et al. 2008; Cassini et al. 2010). Otherwise, Physalaemus aguirrei Bokermann was not recovered nested within this group, contradicting what was suggested in a previous phenetic analysis (Nascimento et al. 2005). Members of the P. olfersii group inhabit the Atlantic rainforest and most of them have a similar advertisement calls with pulsed notes, without frequency modulation and harmonic structure (Giaretta et al. 2009; Cassini et al. 2010; Lourenço et al. 2015). Regarding their larval stage, only P. soaresi, P. maximus, and P. olfersii have their tadpoles described (Weber et al. 2005; Baêta et al. 2007; Giaretta et al. 2009). Physalaemus orophilus occurs in montane Atlantic Forest sites at the eastern slope of the Espinhaço Range in the State of Minas Gerais, southeastern Brazil (Cassini et al. 2010). Herein, we describe the tadpole of P. orophilus from Quadrilátero Ferrífero mountain region, southern limit of the Espinhaço Range and compared it to the known tadpoles of the P. olfersii group.